Student Teachers’ Strategies to Obtain Students’ Attention during Teaching Practice - Gumilar, Bagus Surya; Anisa, Nona; Faturahman, Hanif; Nanda, Dira Aprilia (FOSTER: Journal of English Language Teaching, 2023)
During the teaching and learning process, the teachers must bring students' attention to themselves. The purpose of this study is to investigate the methods that student teachers employ during their classroom teaching practicum to attract their pupils' attention. Researchers used the classroom observation method to investigate each strategy utilized by student teachers. During the observation, student teachers used a combination of verbal and nonverbal strategies to get the students' attention; however, there needs to be follow-up on all of these methods. The conditions, including the level of loudness in the classroom, are why the student teachers had to keep using the same tactics. Clapping and sussing are the most effective methods for obtaining students' attention because of the ease with which it may be transferred to students.